Associations between metabolic dysfunction–associated steatotic liver disease and physical and mental health–related quality of life in older adults - Marzieh Nasr Azadani; Mojtaba Lotfaliany; Najmeh Davoodian; Michael Berk; Robyn L. Woods; Joanne Ryan; John J. McNeil; Julie A. Pasco; Nigel Stocks; Stuart K. Roberts; William Kemp; Ammar Majeed; et al. (GeroScience, 2026)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

Evaluation of a Prefabricated Fish Passage Design for Great Plains Fishes - Ryan M. Fitzpatrick; David W. Longrie; Ryan J. Friebertshauser; H. Paul Foutz (Fishes, 2023)
Connectivity is critical for stream fish persistence, and fish passage structures are a useful conservation tool to reconnect fragmented systems. The design of fish passage structures is a tradeoff between the area available for construction, slope, and costs associated with the structure. The Longrie–Fecteau fish passage structure was designed to be modular, adjustable to barrier-specific needs, and to have a low slope (2%) to pass small-bodied fishes. We evaluated fish passage through this structure in Fountain Creek, Colorado, USA, via a PIT tag mark–recapture study. We documented four native Great Plains fish species successfully ascending the passage structure, with most passage occurring at night. We estimated a 3% probability of a released fish entering the structure, then 89% and 99% passage to the midpoint and exit of the 123 m structure, respectively. Low entrance efficiency was due to low recapture probability of small-bodied study organisms in a relatively large system, and the low percentage of space of the entryway on this barrier (

Uncaptured mercury lost to the environment from waste electrical and electronic equipment (WEEE) in scrap metal and municipal wastes - Yvonne Ryan-Fogarty; Cornelis Peter Baldé; Michelle Wagner; Colin Fitzpatrick (Resources, Conservation and Recycling, 2023)

Elevated Winter Stream Temperatures below Wastewater Treatment Plants Shift Reproductive Development of Female Johnny Darter Etheostoma nigrum: A Field and Histologic Approach - Catherine M. Adams; Dana L. Winkelman; Paula A. Schaffer; Daniel L. Villeneuve; Jenna E. Cavallin; Michael Ellman; Kelvin Santana Rodriguez; Ryan M. Fitzpatrick (Fishes, 2022)
River water temperatures are increasing globally, particularly in urban systems. In winter, wastewater treatment plant (WWTP) effluent inputs are of particular concern because they increase water temperatures from near freezing to ~7–15 °C. Recent laboratory studies suggest that warm overwinter temperatures impact the reproductive timing of some fishes. To evaluate winter water temperature’s influence in the wild, we sampled Johnny Darter Etheostoma nigrum from three urban South Platte River tributaries in Colorado upstream and downstream of WWTP effluent discharge sites. Fish were collected weekly during the spring spawning season of 2021 and reproductive development was determined from histological analysis of the gonads. Winter water temperatures were approximately 5–10 °C greater ~300 m downstream of the WWTP effluent compared to upstream sites, and approximately 3 °C warmer at sampling sites ~5000 m downstream of the effluent discharge. Females collected downstream of WWTP effluent experienced accelerated reproductive development compared to upstream by 1–2 weeks. Water quality, including total estrogenicity, and spring water temperatures did not appear to explain varying reproductive development. It appears that small increases in winter water temperature influence the reproductive timing in E. nigrum. Further investigations into how shifts in reproductive timing influence other population dynamics are warranted.

A critical comparison of integral projection and matrix projection models for demographic analysis: Reply - Daniel F. Doak; Ellen Waddle; Ryan E. Langendorf; Allison M. Louthan; Nathalie Isabelle Chardon; Reilly Dibner; Robert K. Shriver; Cristina Linares; Maria Begoña Garcia; Sarah W. Fitzpatrick; William F. Morris; Megan L. DeMarche (Ecology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Tag retention in and effects of passive integrated transponder tagging on survival and swimming performance of a small‐bodied darter - Tyler R. Swarr; Christopher A. Myrick; Ryan M. Fitzpatrick (Journal of Fish Biology, 2022)
Fisheries biologists have been hesitant to use passive integrated transponder (PIT) tags in small‐bodied fishes (40–200 mm TL) such as darters (Percidae: Etheostomatinae) because of the fishes' size and potential effect on swimming performance. The authors used constant acceleration trials to evaluate the swimming performance of Arkansas darters Etheostoma cragini in control (no incision or tag), sham (incision and suture) or PIT tagged (surgically implanted 8 × 1.4 mm intra‐peritoneal PIT tag) treatments. Tag retention and fish survival were monitored for up to 199 days post‐tagging. Maximum swimming velocity did not differ between control, sham and PIT tag treatments, nor was maximum swimming velocity affected by the tagging procedure. Tag retention was 100%, and the overall survival of tagged fish was 88% in the swimming study, and 100% in the long‐term study, suggesting that small PIT tags are suitable for use in darters. The authors include a brief meta‐analysis on the results reported by 20 studies that PIT tagged small‐bodied fishes, representing 38 species and nine families of freshwater fish.

Behavioral Interactions between a Native and an Invasive Fish Species in a Thermally Heterogeneous Experimental Chamber - Lindsy R. Ciepiela; Ryan M. Fitzpatrick; Samuel T. Lewis; Yoichiro Kanno (Fishes, 2021)
Mechanisms of the displacement of native fish by nonnative fish can include agonistic behaviors that push native fish species out of their preferred habitat, including their thermal optima. To examine these interactions, we built an experimental thermal preference chamber to evaluate: (1) the thermal preference of native, glacial relict northern redbelly dace Chrosomus eos; (2) if the thermal preference and movement changed in the presence of the invasive western mosquitofish Gambusia affinis; and (3) the direction of agonistic interactions. We hypothesized that G. affinis would express agonistic behavior toward C. eos, because G. affinis is widely recognized as an aggressive invader. Given the temperature range of the experimental chamber, i.e., 20–30 °C, C. eos selected an average of 24.3 °C as its thermal preference. After G. affinis’ introduction, the thermal preference of C. eos increased by 1.7 °C and the movement, given by distance (cm) travelled, increased by 21%. Contrary to our prediction, more agonistic interactions were observed in C. eos toward G. affinis. These results indicate that agonistic behavior of G. affinis toward native fish species may be species- and condition-specific, and may not always be the primary mechanism of native species’ displacement. Biological invasions are a global issue and altered thermal regimes are expected to continue. This study provided the novel approach using of a thermally heterogeneous thermal chamber to examine thermal preferences and aggressive interactions between a native and an invasive species. Future research should examine other life history traits that may be conveying the competitive advantage to G. affinis.

Using Isotopic Data to Evaluate Esox lucius (Linnaeus, 1758) Natal Origins in a Hydrologically Complex River Basin - Ryan M. Fitzpatrick; Dana L. Winkelman; Brett M. Johnson (Fishes, 2021)
Otolith microchemistry has emerged as a powerful technique with which to identify the natal origins of fishes, but it relies on differences in underlying geology that may occur over large spatial scales. An examination of how small a spatial scale on which this technique can be implemented, especially in water bodies that share a large proportion of their flow, would be useful for guiding aquatic invasive species control efforts. We examined trace isotopic signatures in northern pike (Esox lucius) otoliths to estimate their provenance between two reservoirs in the Upper Yampa River Basin, Colorado, USA. This is a challenging study area as these reservoirs are only 11-rkm apart on the same river and thus share a high proportion of their inflow. We found that three isotopes (86Sr, 137Ba, and 55Mn) were useful in discriminating between these reservoirs, but their signatures varied annually, and the values overlapped. Strontium isotope ratios (87Sr/86Sr) were different between sites and relatively stable across three years, which made them an ideal marker for determining northern pike provenance. Our study demonstrates the usefulness of otolith microchemistry for natal origin determination within the same river over a relatively small spatial scale when there are geologic differences between sites, especially geologic differences underlying tributaries between sites.

Quantifying WEEE arising in scrap metal collections: Method development and application in Ireland - Yvonne Ryan‐Fogarty; Damian Coughlan; Colin Fitzpatrick (Journal of Industrial Ecology, 2021)

Remanufacture of Hot Forging Dies By LMD-p Using a Cobalt Based Hard-Facing Alloy - Ryan Devine; Crawford Cullen; Jim Foster; Mykola Kulakov; Conor MacFadden; Stephen Fitzpatrick (BHM Berg- und Hüttenmännische Monatshefte, 2021)

Development and Implementation of a Continuing Medical Education Program in Canada: Knowledge Translation for Renal Cell Carcinoma (KT4RCC) - Luke T. Lavallée; Ryan Fitzpatrick; Lori A. Wood; Joan Basiuk; Christopher Knee; Sonya Cnossen; Ranjeeta Mallick; Kelsey Witiuk; Marie Vanhuyse; Simon Tanguay; Antonio Finelli; Michael A. S. Jewett; et al. (Journal of Cancer Education, 2019)

Model selection and assessment for multi‐species occupancy models - Kristin M. Broms; Mevin B. Hooten; Ryan M. Fitzpatrick (Ecology, 2016)
While multi‐species occupancy models (MSOMs) are emerging as a popular method for analyzing biodiversity data, formal checking and validation approaches for this class of models have lagged behind. Concurrent with the rise in application of MSOMs among ecologists, a quiet regime shift is occurring in Bayesian statistics where predictive model comparison approaches are experiencing a resurgence. Unlike single‐species occupancy models that use integrated likelihoods, MSOMs are usually couched in a Bayesian framework and contain multiple levels. Standard model checking and selection methods are often unreliable in this setting and there is only limited guidance in the ecological literature for this class of models. We examined several different contemporary Bayesian hierarchical approaches for checking and validating MSOMs and applied these methods to a freshwater aquatic study system in Colorado, USA, to better understand the diversity and distributions of plains fishes. Our findings indicated distinct differences among model selection approaches, with cross‐validation techniques performing the best in terms of prediction.

Experimental evidence for the effect of habitat loss on the dynamics of migratory networks - Gustavo S. Betini; Mark J. Fitzpatrick; D. Ryan Norris (Ecology Letters, 2015)
Migratory animals present a unique challenge for understanding the consequences of habitat loss on population dynamics because individuals are typically distributed over a series of interconnected breeding and non‐breeding sites (termed migratory network ). Using replicated breeding and non‐breeding populations of Drosophila melanogaster and a mathematical model, we investigated three hypotheses to explain how habitat loss influenced the dynamics of populations in networks with different degrees of connectivity between breeding and non‐breeding seasons. We found that habitat loss increased the degree of connectivity in the network and influenced population size at sites that were not directly connected to the site where habitat loss occurred. However, connected networks only buffered global population declines at high levels of habitat loss. Our results demonstrate why knowledge of the patterns of connectivity across a species range is critical for predicting the effects of environmental change and provide empirical evidence for why connected migratory networks are commonly found in nature.

Lethal Effects of Water Quality on Threatened California Salamanders but Not on Co‐Occurring Hybrid Salamanders - MAUREEN E. RYAN; JARRETT R. JOHNSON; BENJAMIN M. FITZPATRICK; LINDA J. LOWENSTINE; ANGELA M. PICCO; H. BRADLEY SHAFFER (Conservation Biology, 2013)
Biological invasions and habitat alteration are often detrimental to native species, but their interactions are difficult to predict. Interbreeding between native and introduced species generates novel genotypes and phenotypes, and human land use alters habitat structure and chemistry. Both invasions and habitat alteration create new biological challenges and opportunities. In the intensively farmed Salinas Valley, California (U.S.A.), threatened California tiger salamanders ( Ambystoma californiense ) have been replaced by hybrids between California tiger salamander and introduced barred tiger salamanders ( Ambystoma tigrinum mavortium ). We conducted an enclosure experiment to examine the effects habitat modification and relative frequency of hybrid and native California tiger salamanders have on recruitment of salamanders and their prey, Pacific chorus frogs ( Pseudacris regilla ). We tested whether recruitment differed among genetic classes of tiger salamanders (hybrid or native) and pond hydroperiod (seasonal or perennial). Roughly 6 weeks into the experiment, 70% (of 378 total) of salamander larvae died in 4 out of 6 ponds. Native salamanders survived ( n = 12) in these ponds only if they had metamorphosed prior to the die‐offs. During die‐offs, all larvae of native salamanders died, whereas 56% of hybrid larvae died. We necropsied native and hybrid salamanders, tested water quality, and queried the California Department of Pesticide Regulation database to investigate possible causes of the die‐offs. Salamander die‐offs, changes in the abundance of other community members (invertebrates, algae, and cyanobacteria), shifts in salamander sex ratio, and patterns of pesticide application in adjacent fields suggest that pesticide use may have contributed to die‐offs. That all survivors were hybrids suggests that environmental stress may promote rapid displacement of native genotypes . Efectos Letales de la Calidad del Agua sobre Salamandras de California Amenazadas pero no sobre Salamandras Híbridas Concurrentes

A gene family of putative immune recognition molecules in the hydroid Hydractinia - Ryan S. Schwarz; Linda Hodes-Villamar; Kelly A. Fitzpatrick; Matthew G. Fain; Austin L. Hughes; Luis F. Cadavid (Immunogenetics, 2007)